Nuevas posibilidades y retos para la investigación y el conocimiento en universidades (2013)
This article reflects upon the university as an institution that nowadays given its research mission and its subsequent knowledge generation, is subjected to stresses of internal and external origin. External tension comes from the governments which pretend that universities enhance and redirect their research looking for innovative or applied knowledge to social and economic development issues. Internal tension comes from the way in which the university manages the knowledge it generates. This situation requires that the university produces strategies to be socially accepted without leaving aside its principles behind. Consequently, in this article the difficulties and possibilities for conducting this management are mentioned.Keywords: knowledge, innovation, research, university, socioeconomic development.